Job commitment and work attitudes among librarians of universities in Western Visayas and their implications to efficiency and effectiveness - Linaugo, Analiza G.; Obille, Kathleen Lourdes B.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study aimed at determining the job commitment and work attitude of librarians in universities in Western Visayas and their implications to efficient and effective library service. Specifically, it sought to find the following about the librarians: their profile according to age, civil status, length of service, type of institution, educational qualification, and educational attainment; the extent of their job commitment; the prevailing work attitude; the level of their efficiency and effectiveness based on the perception of their immediate unit head or administrators, their peers, and themselves; and the significant relationship between 1) the librarians' job commitment and their age, civil status, length of service, type of institution, educational qualification, and educational attainment; 2) the librarians' job commitment and work attitude; 3) the librarians' job commitment and their efficiency and effectiveness; 4) the librarians' work attitude and their age, civil status, length of service, type of institution, educational qualification, and educational attainment; and 5) the librarians' work attitude and their efficiency and effectiveness.
The respondents of this study consists of librarians and their immediate unit heads or administrators from 12 universities in Western Visayas. Among the many regions of the Philippines, Western Visayas is host to universities which are at par with their counterparts in Metro Manila.
The research was conducted during the first semester of AY 2007-2008. The researcher utilized two sets of survey questionnaires adapted from Dales' (2003) work, Self-assessment Survey on Job Commitment and Work Attitudes, to be answered by librarians, and Evaluation of the Librarians' Efficiency and Effectiveness, to be answered by their immediate unit heads or administrators.
The descriptive survey method was used. As for the statistical methods, the researcher used frequency counts and percentages to establish the profile of librarians. The mean was used to determine their extent of job commitment, prevailing work attitudes, and level of effectiveness and efficiency. To test the significant relationship between the mentioned variables, the Pearson Product Moment of Correlation Coefficient was used. All statistical analyses were done using Microsoft Excel and the Statistical Package for Social Sciences.
As concluded by the study, the librarians in universities in Western Visayas generally exhibit exceptionally high and commendable job commitment. The attitude of the librarians in universities in Western Visayas towards their work is outstanding as reflected in their quality and quantity of work as well as in their cooperation to the related work activities. The efficiency of the librarians in universities in Western Visayas reflected a very good rating from their unit head/unit administrator. The success of the library in universities in Western Visayas depends on the efficiency and effectiveness of librarians' performance of their work. The efficiency and effectiveness will depend on the librarians' job commitment and work attitudes.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Philippines -- Western Visayas; Librarians -- Job satisfaction; Academic libraries -- Philippines -- Western Visayas